Oocyte Meiotic Competence in the Domestic Cat Model: Novel Roles for Nuclear Proteins BRD2 and NPM1 - Chavez, Daniela R.; Lee, Pei-Chih; Comizzoli, Pierre (Frontiers in Cell and Developmental Biology, 2021)
To participate in fertilization and embryo development, oocytes stored within the mammalian female ovary must resume meiosis as they are arrested in meiotic prophase I. This ability to resume meiosis, known as meiotic competence, requires the tight regulation of cellular metabolism and chromatin configuration. Previously, we identified nuclear proteins associated with the transition from the pre-antral to the antral follicular stage, the time at which oocytes gain meiotic competence. In this study, the objective was to specifically investigate three candidate nuclear factors: bromodomain containing protein 2 (BRD2), nucleophosmin 1 (NPM1), and asparaginase-like 1 (ASRGL1). Although these three factors have been implicated with folliculogenesis or reproductive pathologies, their requirement during oocyte maturation is unproven in any system. Experiments were conducted using different stages of oocytes isolated from adult cat ovaries. The presence of candidate factors in developing oocytes was confirmed by immunostaining. While BRD2 and ASRGL1 protein increased between pre-antral and the antral stages, changes in NPM1 protein levels between stages were not observed. Using protein inhibition experiments, we found that most BRD2 or NPM1-inhibited oocytes were incapable of participating in fertilization or embryo development. Further exploration revealed that inhibition of BRD2 and NPM-1 in cumulus-oocyte-complexes prevented oocytes from maturing to the metaphase II stage. Rather, they remained at the germinal vesicle stage or arrested shortly after meiotic resumption. We therefore have identified novel factors playing critical roles in domestic cat oocyte meiotic competence. The identification of these factors will contribute to improvement of domestic cat assisted reproduction and could serve as biomarkers of meiotically competent oocytes in other species.